The Theme of Health in the Letters of Vytautas the Great and his Contemporaries - Čapaitė, Rūta (Senoji Lietuvos literatūra, 2014)
The paper discusses the health-related information found in the letters of the Grand Duke of Lithuania Vytautas the Great, his addressees and addressers. It covers the following issues: whose (from the point of view of an individual’s rank) health was mentioned in letters and why, what information was supplied and in what form (for instance, how diseases or their symptoms were described), and whether the letters contained information directly related to the treatment of health problems. The information found in the letters is supplemented with data from the expenses book of the treasurer of the Teutonic Order and with narratives from chronicles. In addition to the prevailing political realities, Vytautas the Great, his addressees and addressers wrote about their own health (a disease, recuperation, and the like) and that of the people closest to them in their letters and took interest in the state of health of other heads of states or top officials. It was only seldom that a whole letter would deal with health matters: more often than not, such information would be inserted in multi-themed letters. By its nature, the information related to health matters found in the correspondence can be broken down into purely business information, business-personal information, and purely personal information. The symptoms of health conditions mentioned in the letters of Vytautas and his correspondents render the task of identifying the diseases almost impossible. They referred to obvious symptoms characteristic of a number of diseases (for example, internal fever, inability to eat, weakness in the legs) or mentioned general poor health. The symptoms of recuperation were mentioned extremely seldom. Some information on diseases suffered was found in the requests of Vytautas and Jogaila asking the Grand Master to send a doctor of one specialization or another, and in the entries pertaining to doctors’ visits in the book of expenses of the treasurer of the Teutonic Order. However, even in these instances it does not become clear what diseases those doctors treated. Three groups of health disorders can be distinguished on the basis of the analysed sources: those of eyes, legs, and internal organs. It was impossible to identify the conditions of eyes and legs. Hypothetically, disorders of legs are linked to two factors: various injuries and internal diseases. Presumably, leg disorders related to internal diseases were either disorders related to legs only, or the symptoms or consequences of internal diseases. It was impossible to find out in greater detail what internal diseases were suffered. Only the disease of the Grand Master Konrod von Jungingen was identified. The following symptoms mentioned in the letters are related to internal diseases: internal fever, an inability to eat, weakness in the legs, a prolonged sick condition, or a prolonged unstable health condition. Doctors of three specializations are mentioned in the correspondence and in the book of expenses of the treasurer of the Teutonic Order: an eye doctor (ogenarzt), a wound doctor (wundarzt), and a doctor of internal diseases (leiparczt). In the book of expenses of the Order’s treasurer, arzt referred to the individuals identified with the doctors of internal diseases. Vytautas and his correspondents knew about famous doctors and asked for them to be sent over when a need arose. There is hardly any mention of the methods of treatment in the analysed sources. However, the book of expenses of the Order’s treasurer contains a fair amount of data on money spent on medicines. Nothing is said in the letters of Vytautas and his correspondents about doctors’ remuneration. The entries in the book of expenses of the Order’s treasurer show that a doctor was paid an annual salary and remunerated for the treatment of one or another individual. It is difficult to say, however, what factors determined the size of remuneration: the time of treatment, the patient’s condition, or other reasons.